EXPERIMENT ON THE DEVELOPMENT OF PHYSICAL TRAINING BY POSSESSION DRILLS FOR JUNIORS PLAYERS UNDER 15 - Savu Vasile Catalin; Ploesteanu Constantin (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2015)
The training period of young soccer players is long and difficult and it has been proved that the most difficult periods for accumulations are the pre-puberty and the puberty periods. In order to have access to high performance it is of utmost importance to have knowledge of the modern ways and methods of training the young players. This is the prerequisite, the starting point of this experimental study. The training concept reflects the coach's attitude, conception and action with respect to the pedagogical process of physical, technical and psychological training as well as to the complex training meant to pave the way to high performance for the promising children.